2020
DOI: 10.1073/pnas.2020619117
|View full text |Cite
|
Sign up to set email alerts
|

FXR mediates T cell-intrinsic responses to reduced feeding during infection

Abstract: Reduced nutrient intake is a widely conserved manifestation of sickness behavior with poorly characterized effects on adaptive immune responses. During infectious challenges, naive T cells encountering their cognate antigen become activated and differentiate into highly proliferative effector T cells. Despite their evident metabolic shift upon activation, it remains unclear how effector T cells respond to changes in nutrient availability in vivo. Here, we show that spontaneous or imposed feeding reduction duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 41 publications
0
9
1
Order By: Relevance
“…Also the interaction between BAs and CD8 + T cells has been investigated insufficiently. Both the involvement of CD8 + T cells in controlling the BA synthesis by inducing cholangitis and the effect of FXR deletion on T cell fitness were described previously ( Glaser et al, 2019 ; Campbell et al, 2020a ). In addition, a recent study has revealed accumulation of CXCR6 + auto-aggressive CD8 + T cells in the liver of mice and patients suffering from NASH ( Dudek et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also the interaction between BAs and CD8 + T cells has been investigated insufficiently. Both the involvement of CD8 + T cells in controlling the BA synthesis by inducing cholangitis and the effect of FXR deletion on T cell fitness were described previously ( Glaser et al, 2019 ; Campbell et al, 2020a ). In addition, a recent study has revealed accumulation of CXCR6 + auto-aggressive CD8 + T cells in the liver of mice and patients suffering from NASH ( Dudek et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunity and metabolism are mutually exclusive in that setting, with interferon-inducible immune response pathways upregulated at the expense of lipid metabolism (Han et al, 2017;Shulzhenko et al, 2011). The process of energy prioritization must be tightly regulated, with evidence indicating that T cell responses are physiologically dampened to limit the amount of energy they consume, thereby preventing excessive weight loss (Campbell et al, 2020). We will next discuss how the immune system integrates dietary cues to tune responses based on the nutritional status of the host and how trade-offs and priorities emerge when resources are severely limited.…”
Section: Severe Nutritional Stress Induces Prioritization Of Defined ...mentioning
confidence: 99%
“…Then, glutamine is further deaminated into glutamate by glutamate synthase (GS) in a MYC-dependent pathway ( 31 , 49 ). Glutamate can be converted to α-ketoglutarate, which enters the tricarboxylic acid (TCA) cycle as an anaplerosis source to meet the biosynthetic and energy demands for T cells activation, especially under a glucose-restricted condition ( 52 ). Glutamate can also promote T cell activation by influencing the metabolism of other biomolecules, including nucleotide, fatty acids and amino acids ( 53 ).…”
Section: The Role Of Metabolic Reprogramming In T Cell Activation And...mentioning
confidence: 99%